The Role of Self-Determination Theory in Shaping Investment Readiness Among Young Investors - Basri Bado; Hajar Dewantara (Global Research Collaboration, 2024)
This study explores the investment readiness of students from the Faculty of Economics and Business at Universitas Negeri Makassar using the Self-Determination Theory (SDT) framework. Both intrinsic and extrinsic motivation were found to play crucial roles in influencing investment readiness. Intrinsic motivation drives students to develop their knowledge and skills, while extrinsic motivation is triggered by financial rewards and social recognition. The main barriers identified include low financial literacy, limited access to information, and resistance to new technologies. The study suggests that enhancing financial education and digital literacy through comprehensive programs and supportive environments is essential to overcoming these obstacles and improving students' investment readiness. By addressing these barriers, educational institutions can better prepare young investors for successful financial decision-making, equipping them with the necessary tools and confidence to navigate the investment landscape.